Microenseñanza en el laboratorio de ciencias para el alumnado del grado de educación infantil - Dulsat-Ortiz, Carles (Revista Científica, 2019)
This research aims to approach learning from the pillars of Delors in a space as specific as the science laboratory as well as the application of the concept of Chevallard’s didactic transposition. For this, it approaches the use of the active methodology: micro-education. The approach of this microteaching is oriented to introduce scientific knowledge and show them through experiments to the rest of the class group. Therefore, the purpose of this research is to describe from the point of view of students the experiences of this methodology and the advantages of this more participatory methodology. The method used for the collection and subsequent analysis of the information followed a non-experimental only post-test methodology with a non-equivalent and unique group, being the invited population the students of second A of the degree of infantile education in the Coruña University. Among the results, we highlight the high degree of acceptance of the methodology and how it has managed to increase the degree of initial acceptance towards the natural sciences. Among the conclusions, it should be noted that the methodology was successful in its application because students showed it in their answers, also because of the increase in the approach to science and acquisition of different knowledge.